Sexuality, Erotic Transference/Countertransference, and the Clinical Third - Strawn, Brad D. (Journal of psychology and christianity, 2022)
This article explores issues of enactment and complementarity especially probable when sexuality and erotic transference/countertransference enter the clinical space. The clinical concepts of the Third and mutual recognition will be offered both as means to conceptualize these potentially anxiety-provoking encounters and working through potential impasses of doer-and-done-to. A clinical consultation will be used to illustrate the process. Sexuality has a long history of being problematized in many religious traditions, which may contribute to its avoidance in clinical integrative practice. It is essential that sexuality be brought back into therapy as a kind of missional practice of redeeming what has once been disavowed, disowned, and denied.